Analisis Problematika Pelaksanaan Supervisi dalam Kegiatan Pembelajaran pada Masa Pandemi COVID-19 di MI - Halimatussa’diyyah, Halimatussa’diyyah; Gumiandari, Septi (IAIN Syekh Nurjati Cirebon, 2021)
The implementation of academic supervision is one of the important things to do. With the implementation of supervision, it is hoped that it can provide assistance and breakthrough solutions to educational problems and improve the performance of teachers in the learning process. This study aims to determine the problems with the implementation of academic supervision during the Covid-19 pandemic at MI Islamiyah Cirebon. To achieve this goal, this study uses a qualitative approach with phenomenological descriptive analysis. Data collection techniques were carried out through interviews and documentation studies. To obtain comprehensive data, researchers used triangulation to support the credibility and validity of the data obtained. The results of the study stated that: (1) the problems found in implementing academic supervision during the Covid-19 pandemic are the difficulty in implementing the national curriculum in the midst of the Covid-19 pandemic, teachers’ unpreparedness in carrying out online learning, teachers; technology savvy, technical differences in the implementation of learning for each school that cause contra for the parents, understanding of the material which cannot be absorbed optimally, teachers’ difficulty in assessing the development of students' affective attitudes; (2) efforts to overcome the problems of academic supervision are replacing the national curriculum with the Covid-19 emergency curriculum, providing guidance and direction related to the use of technology, and implementing face-to-face learning twice a week.